Web-Based Student's Recipe E-Book System - Zuhayra Nasrin Zul Hsham,; Nayef Abdulwahab Mohammed Alduais, (Applied Information Technology And Computer Science, 2023)
The Web-based Student's Recipe E-book system has been successfully implemented, effectively fulfilling user requirements, and offering a convenient solution for discovering recipes and maintaining a healthy lifestyle. Developed using CSS, HTML, PHP, JavaScript, and Visual Studio Code, the system features a user-friendly interface that facilitates recipe exploration and promotes healthy cooking choices. Thorough testing was conducted to ensure the system's functionality, usability, and performance, resulting in a valuable resource for students and individuals seeking nutritious meal options. Based on the testing that involved seven students, feedback confirmed the system's usability, and user satisfaction, and identified areas for improvement, such as search functionality, recipe categorization, and bookmarking features. Overall, more than 90 percent of the test passed successfully, with a few exceptions. Despite the presence of certain flaws, such as limited customization options, insufficient community interaction, and irregular updates, the Web-based Student's Recipe E-book system has the potential for further improvement.